Rigidités discursives et flou sémantique - Pineira-Tresmontant, Carmen (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Through a computerized description of trade-union texts, an attempt has been made to automatically isolate and record complex units called “lexies”. Such an endeavour highlights the difficulties met when identifying and making a list of such units. By restricting our scope to the category of syntactical lexies, we evaluate their importance in relation with the size of the text. A detailed analysis of a category of lexies is proposed, i.e. complex predetermination. The link between the characteristics of predetermination and discourse semanticism is studied in relation with the concept of “langue de bois”, which stresses semantic vagueness.
Keywords: “langue de bois”; trade-union texts